The future of community how to leverage Web3 technologies to grow your business - Kraski, John; Shenkarow, Justin; Adkins, Charles (John Wiley, 2023)
A penetrating look at how web3 will shape our shared future In The Future of Community: How to Leverage Web3 Technologies to Grow Your Business, a team of web3 visionaries and tech-savvy executives delivers a groundbreaking new take on the seismic impact web3 is having--and will continue to have--on our technological and social landscapes. The authors discuss why web3 really is the "next big thing" to shape our digital and offline futures and how it will transform the world. You'll discover a whole host of web3 applications poised to excite and disrupt industries around the world, from fan tokens that reshape how we think about interactions between artists and fans to self-sovereign identities on the blockchain that allow you to take full control over how your personal data is used and collected online. You'll also find: Insightful explorations of technologies and techniques like tokenization, decentralized marketplaces, decentralized autonomous organizations, and more Explanations of how web3 allows you to take greater ownership and control of your digital and offline assets Discussions of why web3 increases transparency and accountability at every level of business, government, and social hierarchies An invigorating and singularly incisive resource, The Future of Community is a can't-miss book for futurists, entrepreneurs, founders, business leaders, tech enthusiasts, and web3 fans excited about today's cutting-edge tech and how it will shape our tomorrows.
Keywords: Technological innovations -- Economic aspects; Social media -- Economic aspects; Innovations; Aspect économique; Médias sociaux; Aspect économique